The Concept Of Sulh-E Kul (Universal Peace) Of Jalaluddin Akbar And Its Relevance For Nowadays (Ushuluddin International Conference (USICON), 2017)
Religion is often blamed as the main trigger of social conflict. It is even being brought into political contestation and is used as the tool to defeat the political opponents. This situation has been happened throughout the time, and is getting arise nowadays especially in the country where Islam is the major religion. In such situation, the role of government and ruler in spreading tolerance and peace are really needed for the betterment of society. This paper will elaborate about the concept of Sulh-e Kul (Universal Peace) of Jalaluddin Akbar, and its relevance for nowadays. Being situated in the middle of multi-religious society, Akbar
Keywords: Peace, Tolerance, Harmony, Jalaluddin Akbar, Sulh-e kull, Universal Peace